Overview of Distribution of Medicines and Consumable Medical Materials (Bmhp) from Pharmacy Warehouse Pharmacy Depot to Inpatient Installations of Diseases in General Hospital in South Tangerang City in 2021 - Rika Rakasiwi; Noo Latifah Amin (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
The problem in distributing pharmaceutical preparations that often occur in hospitals is when medicines arrive late at the hospital pharmacy depot/satellite. Not only employees who feel loss but patients who need medicines are even more harmed because they have to wait for the medicine that comes too late. The type of research used in this study is descriptive qualitative research using case study design. Primary data is obtained from direct observations and in-depth interviews and document studies. This research was conducted in South Tangerang City Hospital from May to June 2021. Based on the results of research obtained for input obtained human resources results in pharmaceutical warehouses are not adequate, infrastructure to distribute medicines and medical materials consumables to the room has not been up to standard. In the process obtained results that have been done by the distribution flow of drugs and medical materials consumables. In the output obtained results there is still a void of drugs. Conclusion In the input of human resources in the Pharmacy Warehouse is not adequate, the infrastructure in distributing medicines and medical materials consumables to the room has not been up to standard. The distribution process has been carried out by the standards of operational procedures in force. At the output is still the discovery of empty drug stocks. Suggest the head of the warehouse to be able to supervise the SOP that the distribution of drugs and BMHP. The need to hold a special trolley addition in the Pharmacy Warehouse to facilitate the distribution of drugs and medical materials consumables.